A case of tri-segmental cranial nerve V herpes zoster. (2019) - Cheema, Hena S.; Diedrich, Aloise M.; Kyne, Briana M.; Toeque, Mona
Abstract: Varicella-zoster is the causative virus underlying varicella or "chickenpox" and herpes zoster or "shingles." Cases of disseminated disease have been widely reported in immunocompromised patients. We describe an interesting case of tri-segmental cranial nerve V herpes zoster here with discussion of the salient clinical features as well as brief discussion about ongoing trials for herpes zoster ophthalmicus prophylaxis. This case also highlights the importance of timely treatment and diagnosis, as the patient presented 6 days prior to hospitalization with a mild vesicular facial rash but was lost to follow up without filling a prescription for acyclovir, returning with severe facial involvement.